″Training of future railway workers in Germany: educational activity of Doutche Bahn AG″ - Baglaj, V. (Problems of Engineer-Pedagogical Education, 2018)
Presently in Germany, as well as in other countries of Western Europe, there is an adverse demographic situation which is caused by the decrease and aging of the native local population. It has negatively affected the results of work of one of the most powerful national railway operators of Germany – Doutche Bahn AG. Under such circumstances vocational training of future railway workers, vocational counselling of the young and their acquaintance with the geography of railway trades have become of crucial importance for successful development of the railway transport of the country. The article explains that the innovative vocational counseling measures used by Doutche Bahn AG are entirely comprehensible to the selection system typical of vocational educational institutions of Ukraine which specialize in railway engineering. Both models of training future railway workers, which exist today in Germany (the classical model of vocational training of the young and the model of training of railway workers from among the unemployed who have technical education), can be applied successfully in Ukraine. Target vocational training of future railway workers is carried out in educational institutions of Germany basing on the model of the professional activity of future experts which incorporates elements of the dual system of vocational training and is considered rather promising in domestic vocational technical educational institutions which specialize in railway engineering.